A Critical Review: Coupling and Synchronization Analysis Methods of EEG Signal with Mild Cognitive Impairment - Wen, Dong; Zhou, Yanhong; Li, Xiaoli (Frontiers in Aging Neuroscience, 2015)
At present, the clinical diagnosis of mild cognitive impairment (MCI) patients becamebecomes the important approach of evaluating early Alzheimer’s disease. The methods of EEG signal coupling and synchronization act as a key role in evaluating and diagnosing MCI patients. Recently, these coupling and synchronization methods were used to analyze the EEG signals of MCI patients according to different angles, and many important discoveries have been achieved. However, considering the one-sidedness of the methods themselvesthat every method is single-faceted in studying questionssolving problems, these methods exist different deviations and errors invarious deficiencies when analyzing EEG signals of MCI patients. This paper reviewed in detail the coupling and synchronization analysis methods, and describedanalyzed their advantages and disadvantages. And the, and proposed a few research questions needed to solve in the future. Also the principles and best performances of these methods were proposeddescribed. It is expected that the performance analysis of these methods can provide the theoretical basis for the method selection of analyzing EEG signals of MCI patients and the future research directions.